Solar PV and grid-connected electricity system with multiple modes operation for homes and buildings - Rosnazri, Ali; Ismail, Daut, Prof. Dr.; Soib, Taib, Assoc. Prof. Dr.; Tunku Muhammad Nizar, Tunku Mansur; Nor Hanisah, Baharudin (Praise Worthy Prize S.r.l., 2013)
Link to publisher's homepage at http://www.praiseworthyprize.com/